Constraints on primordial black hole dark matter from wide binaries in the galactic halo - Tyler, Emily Sarah (2022)
Primordial black holes (PBHs), black holes that are formed in the early Universe from the collapse of over-densities, are a candidate for non-baryonic cold dark matter. The fraction of dark matter made up of PBHs has been constrained using multiple mechanisms including evaporation, gravitational lensing, gravitational waves from mergers, large-scale structure, accretion and the disruption of wide binaries. In this thesis we review the work on wide binaries and improve the reliability of these constraints, primarily by introducing a more physically motivated initial semi-major axis distribution for our simulated binaries.